Analgesic Efficacy of Ultrasound Guided Interscalene Block in Shoulder Scopy Surgeries with 0.2% Ropivacaine with Dexmedetomidine– A Case Series - Dr. Subhashree J,; Dr. Ashalatha P,; Dr. Girija Kumari,; Dr. Manasa Vijay, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Shoulder arthroscopy procedure has becoming popular both as a diagnostic and therapeutic tool in shoulder injuries. Interscalene block provides adequate analgesia as shoulder receives most of its nerve supply through suprascapular and axillary nerves. Our aim is to study the efficacy of ultrasound guided interscalene block in shoulder scopy surgeries in terms of duration of analgesia and opioid requirement in the first 24hrs postoperative period. After obtaining institutional ethics committee approval and written informed consent, We included 40 patients belonging to ASA PS1 and 2. All the patients were induced with propofol 1mg/kg, neuromuscular blockade with rocuronium 1mg/kg, analgesia with fentanyl 2µg/kg, intubated and maintained with oxygen, nitrous oxide and sevoflurane with MAC of 1.5. Then patient received ultrasound guided interscalene block using 15ml 0.2% ropivacaine with 10µg dexmedetomidine. Haemodynamic parameters were noted every 15min till the end of the procedure. Intravenous paracetamol 1g was given at the end of procedure. After extubating and shifting to postoperative period, analgesia was assessed using VAS score at 0hr, 6hr, 12hr, 24hr. Fentanyl 1µg/kg was given when the VAS score was more than 5 and the time to first analgesic request and the total dose given were noted. We found that mean duration of the analgesia was 715.9 ± 261.6 (mean ± SD) minutes and the total analgesic requirement was not more than 2µg/kg fentanyl in the first 24hrs postoperative period. We concluded that ultrasound guided interscalene block with dexmedetomidine provides prolonged and effective analgesia in shoulder scopy surgeries without significant complications.